The Antecedents of the Rural Bank Patronage in Indonesia - Hayati, Sri; Setyanto, Refius Pradipta (Universitas Mercu Buana, 2024)
Objectives: The objective of the studies is to test the causal models of rural banking patronage behavior are still under research and this study is also aimed at filling the empirical gap. This study operationalizes constructs that better reflect the characteristics and uniqueness of rural banking business processes.Methodology: Data collection was carried out directly by distributing questionnaires to consumers or customers of BPR BKK banks in Banyumas Regency, Purbalingga Regency, and Banjarnegara Regency. The number of samples in this study was determined by the purposive sampling method of as many as 373 people. The analysis tool used is Structural Equation Modeling (SEM) and processed using AMOS software.Finding: The findings of this study stated, among others, the following: (1) Relational benefits have a positive effect on business friendship (2) Relational benefits have a positive effect on brand intimacy (3) Business friendship mediates the effect of relational benefits on brand intimacy (4) Business friendship has a positive effect on brand intimacy (5) Brand intimacy has a positive effect on patronage intention.Conclusion: Customer loyalty to the bank greatly determines the sustainability of the bank's business, especially rural banks which generally have fewer resources than national banks. This study confirms the importance of bank management paying attention to five antecedent variables, namely relational benefits (symbiotic benefits, special treatment benefits, and confidence benefits), business friendships, and brand intimacy.